Plasma parameters and the reduction potential at a plasma–liquid interface. Issue 23 (6th June 2022) - Oldham, Trey; Yatom, Shurik; Thimsen, Elijah
Abstract : Experimental measurements of the reduction potential at a plasma–liquid interface are compared to a model-predicted value determined using the plasma parameters obtained via laser Thomson scattering. Abstract : Nonthermal plasmas in contact with liquids have been shown to generate a variety of reactive species capable of initiating reduction–oxidation (redox) reactions at the electrochemically active plasma–liquid interface. In conventional electrochemical cells, selective redox chemistry is achieved by controlling the reduction potential at the solid electrode–electrolyte interface by applying a bias via an external circuit. In the case of plasma–liquid systems, an analogous means of tuning the reduction potential near the interface has not clearly been identified. When treated as a floating surface, the liquid is expected to adopt a net negative charge to balance the flux of hot electrons and relatively cold positive ions. The reduction potential near the plasma–liquid interface is hypothesized to be proportional to the floating potential, which can be approximated using an analytical model provided the plasma parameters are known. Herein, we present a framework for correlating the electron density and electron temperature of a noble gas plasma jet to the reduction potential near the plasma–liquid interface. The plasma parameters were acquired for an argon atmospheric plasma jet in contact with an aqueous solution by means of laser Thomson scattering. The reduction potential was determined using identical reference electrodes to measure the potential difference between the plasma–liquid interface and bulk solution. Interestingly, the measured reduction potentials near the plasma–liquid interface were found to be in good agreement with the model-predicted values determined using the plasma parameters obtained from the Thomson scattering experiments.